Multidrug-Resistant (MDR) Acinetobacter: a Major Nosocomial Pathogen Challenging Physicians (Bangladesh Journal of Medical Microbiology, 2016)
No Abstract AvailableBangladesh J Med Microbiol 2007; 01 (02): 65-68